2015
DOI: 10.1111/jpi.12236
|View full text |Cite
|
Sign up to set email alerts
|

Placental melatonin system is present throughout pregnancy and regulates villous trophoblast differentiation

Abstract: Melatonin is highly produced in the placenta where it protects against molecular damage and cellular dysfunction arising from hypoxia/re-oxygenation-induced oxidative stress as observed in primary cultures of syncytiotrophoblast. However, little is known about melatonin and its receptors in the human placenta throughout pregnancy and their role in villous trophoblast development. The purpose of this study was to determine melatonin-synthesizing enzymes, arylalkylamine N-acetyltransferase (AANAT) and hydroxyind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 68 publications
2
65
0
9
Order By: Relevance
“…Concerning the current research results, we speculate strongly that supplementary antioxidant therapy including Se, Zn, Cu, Mn, ascorbate, GSH, and αtocopherol, as well as melatonin, may be beneficial to such patients during pre-conception and the first-trimester post-conception. 87 Melatonin regulates endometrial morphology and embryo implantation, and is beneficial to a successful pregnancy possibly via F I G U R E 4 Melatonin is a therapeutic agent for endometriosis. 83 It has been further demonstrated that, under specific condition, melatonin treatment could significantly improve fertilization and pregnancy rates.…”
Section: Mel Atonin and Recurrent S P Ontaneous Abortionmentioning
confidence: 99%
“…Concerning the current research results, we speculate strongly that supplementary antioxidant therapy including Se, Zn, Cu, Mn, ascorbate, GSH, and αtocopherol, as well as melatonin, may be beneficial to such patients during pre-conception and the first-trimester post-conception. 87 Melatonin regulates endometrial morphology and embryo implantation, and is beneficial to a successful pregnancy possibly via F I G U R E 4 Melatonin is a therapeutic agent for endometriosis. 83 It has been further demonstrated that, under specific condition, melatonin treatment could significantly improve fertilization and pregnancy rates.…”
Section: Mel Atonin and Recurrent S P Ontaneous Abortionmentioning
confidence: 99%
“…ASMT is Involved in placental melatonin synthesis (Iwasaki et al, 2005) and melatonin regulates trophoblast differentiation (Soliman et al, 2015). Secretin (SCT) is also localised in this organ (Knox et al, 2011).…”
Section: Genes Involved In Placental Functionmentioning
confidence: 98%
“…Simultaneously, melatonin, as a seasonal factor, has been suggested to be involved in a successful pregnancy [62][63][64]. Το be brought to safe conclusions we should carefully consider the pathophysiologic process taking place in preeclampsia (Figure 3).…”
Section: Is a Dysfunction Of The Placental Clock Related To Preeclampmentioning
confidence: 99%